1978
DOI: 10.1139/v78-336
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis rates in aqueous – organic mixed solvents. V. Kinetics of the alkaline decarboxylation of trichloroacetate ion in water – ethanol solutions

Abstract: EL-HUSSIENY M. DIEFALLAH and A. M. EL-NADI. Can. J. Chem. 56,2053Chem. 56, (1978. The kinetics of the alkaline decarboxylation of trichloroacetate ion in ethanol-water solutions have been studied over the temperature range 35.0 t o 70.0nC. The rate of reaction is first order with respect to the trichloroacetate ion and is independent of the concentration of t h e hydroxide ion. The reactivity is enhanced by increasing the concentration of ethanol in t h e water-ethanol solutions and the rate of reaction varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
5
1
Order By: Relevance
“…This result is not in concordance with the postulated reaction mechanism, according to which we expect that the volume of the transition state to be greater than the reactant state, the volume of activation to be positive, and the internal pressure of the reactant ion to be higher than that of the activated complex [5,6].…”
contrasting
confidence: 73%
See 4 more Smart Citations
“…This result is not in concordance with the postulated reaction mechanism, according to which we expect that the volume of the transition state to be greater than the reactant state, the volume of activation to be positive, and the internal pressure of the reactant ion to be higher than that of the activated complex [5,6].…”
contrasting
confidence: 73%
“…Experimentelly, it is found that the rate of reaction decreases with increasing the dielectric constant of the medium; however, the plot of log k versus D _1 does not give rise to a straight line over the whole range of solvent composition [6]. The results may be approximated to the straight line relationship for solvent mixtures with less than about 0.7 water mole fraction, and over this linear portion of the curve it may be assumed that the reaction occurs in a structureless medium and that the simple electrostatic theory may be holding.…”
Section: Ze Oomentioning
confidence: 91%
See 3 more Smart Citations